Financial institutions and their significance in the development of modern financial market of Ukraine. (Economics and region, 2016)
The essence of financial institutions and their role and importance in the development of modern financial market of Ukraine. Defined financial market as an economic category - a system of financial and economic relations between the state, enterprises, public (citizens) on the storage, use and redistribution of financial resources in full economic independence and self-regulation mechanism of market economy. Highlight and revealed three main groups of financial institutions, financial intermediaries; international financial institutions; financial institutions regulators. It was concluded that to further development of the financial market of Ukraine in conditions of financial globalization must implement a set of measures to enhance the participation of financial institutions in promoting domestic business (in particular SME sector), support for research, innovation and more. On the other hand, the implementation of a number of institutional, legal and organizational measures greatly facilitate the role of financial institutions in the development of Ukraine's financial market today.
Keywords: finance; financial markets; financial institutions; financial intermediaries; international financial institutions; financial institutions; regulators; the financial system